Activity-Based Costing and performance: empirical study in the context of Moroccan companies - HAJJI, Zouhair; FARRAT, Outmane (Revue du contrôle, de la comptabilité et de l’audit, 2022)
Following the evolution of companies’ economic and organizational environment, the ability of traditional cost calculation systems to provide relevant information for decision-making has been questioned by the majority of researchers in management accounting. The work carried out in this context led to the proposal of a new method for calculating costs, namely: Activity- Based Costing. Since its appearance, many studies have been carried out on the theoretical foundations, the adoption determinants, the success factors of implementation and the impact of this method on companies’ performance. Through this work, our objective is to take part in the work on the consequences of activity-based costing adoption on performance, in particular at the level of Moroccan companies. The results of our analysis based on a sample of 73 Moroccan companies indicate a positive and statistically significant association between activity-based costing and organizational objectives achievement in terms of cost reduction, product/services’ quality improvement, production and delivery times reduction, guiding employee behavior and productivity growth.